EVALUATION OF ANTI-OXYTOCIC ACTIVITY OF ASPARAGUS RACEMOSUS - JINISH JOSE; KALA KESAVAN P (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to evaluate the anti-oxytocic activity of ethanolic extract of Asparagus racemosus root. Methods: Ethanolic extract of A. racemosus root was taken by Soxhlet extraction method. Wistar strain albino non-pregnant female rats of weight 200–300 g were pre-treated with estrogen and were sacrificed to take their uterus. The tissue was then mounted in an organ bath containing de Jalon’s solution. The response of the tissue to various doses of oxytocin alone and then on adding increasing doses of the alcoholic extracts of A. racemosus along with the dose of oxytocin which produces sub-maximal contraction were recorded on a smoked drum. Results: Extract in doses up to 40 mg when given along with oxytocin 0.1 unit produced graded increase in contractions in rat uterus. From 80 mg onward graded blockade of contractions occurred with complete blockade at 200 mg. On complete removal of the extract by thorough washing, it was seen that oxytocin was again able to produce contractions of the rat uterus tissue. Conclusion: The ethanolic extract of A. racemosus root had demonstrated good anti-oxytocic property.